2018
DOI: 10.12659/msm.912689
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Pelvic Floor Muscle During Ankle Posture Change on the Basis of a Three-Dimensional Motion Analysis System

Abstract: BackgroundWeak pelvic floor muscles (PFMs) is an important cause of stress urinary incontinence. Effective strengthening of PFMs is very helpful in improving lower urinary tract disease. The purpose of this study was to determine the activation of PFMs in accordance with movement of the pelvis and ankle.Material/MethodsFifty healthy adults who underwent PFM contraction in ankle posture change (dorsiflexion, neutral, and plantar flexion) while standing were simultaneously measured using electromyography and mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…In previous studies, artificial fixation with the ankle in PF and standing position kept the coccyx moving forward due to the posterior tilt of the pelvis, resulting in shortening of the muscle fibers of the pelvic floor [6,1820]. However, Lee [12] found that there was no pelvic movement while moving in real time, rather than that in the fixed ankle position; that is, when moving the ankle from neutral position to PF. The problems caused by incontinence in daily life are more likely to occur during natural movements than in fixed positions [12].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous studies, artificial fixation with the ankle in PF and standing position kept the coccyx moving forward due to the posterior tilt of the pelvis, resulting in shortening of the muscle fibers of the pelvic floor [6,1820]. However, Lee [12] found that there was no pelvic movement while moving in real time, rather than that in the fixed ankle position; that is, when moving the ankle from neutral position to PF. The problems caused by incontinence in daily life are more likely to occur during natural movements than in fixed positions [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, Lee [12] found that there was no pelvic movement while moving in real time, rather than that in the fixed ankle position; that is, when moving the ankle from neutral position to PF. The problems caused by incontinence in daily life are more likely to occur during natural movements than in fixed positions [12]. This is because urine leakage occurs due to changes in posture and pressure during continuous movement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations